Anticipated survival and health behaviours in older English adults: cross sectional and longitudinal analysis of the English Longitudinal Study of Ageing. - Jean Adams; Elaine Stamp; Daniel Nettle; Eugene M G Milne; Carol Jagger (PLoS ONE)
Background Individuals may make a rational decision not to engage in healthy behaviours based on their assessment of the benefits of such behaviours to them, compared to other uncontrollable threats to their health. Anticipated survival is one marker of perceived uncontrollable threats to health. We hypothesised that greater anticipated survival: a) is cross-sectionally associated with healthier patterns of behaviours; b) increases the probability that behaviours will be healthier at follow up than at baseline; and c) decreases the probability that behaviours will be 'less healthy' at follow than at baseline. Methods Data from waves 1 and 5 of the English Longitudinal Survey of Ageing provided 8 years of follow up. Perceptions of uncontrollable threats to health at baseline were measured using anticipated survival. Health behaviours considered were self-reported cigarette smoking, physical activity level, and frequency of alcohol consumption. A wide range of socio-economic, demographic, and health variables were adjusted for. Results Greater anticipated survival was cross-sectionally associated with lower likelihood of smoking, and higher physical activity levels, but was not associated with alcohol consumption. Lower anticipated survival was associated with decreased probability of adopting healthier patterns of physical activity, and increased probability of becoming a smoker at follow up. There were no associations between anticipated survival and change in alcohol consumption. Conclusions Our hypotheses were partially confirmed, though associations were inconsistent across behaviours and absent for alcohol consumption. Individual assessments of uncontrollable threats to health may be an important determinant of smoking and physical activity.